• Упростите выражение:

    a)sin(3п/2-a)-cos(п+а)

    б)tg(п+a)+ctg(п/2-a)

    в)sin2a+(sina-cosa)^2

    г)(ctga-tga)tg2a

    Спасибо.

Ответы 1

  • a)sin(3п/2-a)-cos(п+а)=-cos a+cosa=0б)tg(п+a)+ctg(п/2-a)=tg a+tga=2tg aв)sin2a+(sina-cosa)^2=2sin a·cosa+sin²a-2sina·cosa+cos²a=sin²a+cos²a=1г)(ctga-tga)*tg2a= \frac{(ctga-tga)*2tga}{1-tg^{2}a} = \frac{2tga*ctga-2tg^{2}a}{1-tg^{2}a} = \\ 
 \frac{2-2tg^{2}a}{1-tg^{2}a} = \frac{2(1-tg^{2}a)}{1-tg^{2}a} = 2 \\
    • Автор:

      buzzpbfv
    • 5 лет назад
    • 0
  • Добавить свой ответ

Войти через Google

или

Забыли пароль?

У меня нет аккаунта, я хочу Зарегистрироваться

How much to ban the user?
1 hour 1 day 100 years